Determinan Stunting pada Balita Di Puskesmas Wilayah Kabupaten Tangerang Tahun 2020 - Dorsinta Siallagan; Desi Rusiana; Ela Susilawati (Indonesian Journal of Midwifery (IJM), 2021)
The problem of stunting is one of the nutritional problems faced in the world, especially in poor and developing countries. Toddlers with stunting are more at risk of having a low Intelligence Quotient compared to toddlers who are growing well. In 2018, the prevalence of stunting in Tangerang Regency (38%) was higher than the national prevalence (30.8%). This study aims to determine the most dominant factor in the incidence of stunting in the Tangerang District Public Health Center. The research method used was descriptive analytic with a cross sectional study approach. Research Location at the Rajeg Community Health Center, Tangerang Regency. The population in this study were all toddlers who were stunting as many as 211 and a sample of 138 respondents. Sampling using accidental sampling technique. The results showed that stunting was very short at 28.2%. Bivariate analysis using the Chi-Square test. There was a significant relationship between age (p = 0.000), knowledge (p = 0.000), history of ANC (p = 0.023), LBW (p = 0.005) exclusive breastfeeding (p = 0.001), dietary habits (p = 0.005) and history of disease (p = 0.005) with incidence of stunting. The multivariate results showed that the most dominant factor in the incidence of stunting was the high risk age at pregnancy with an OR of 9,333. It is hoped that government programs through related agencies, health workers provide counseling about high-risk age during pregnancy, run the 4T program so that women do not get pregnant when they are too young, too old, too close to birth distances and too many children, other government programs such as Age Maturation Marriage